PENGEMBANGAN MEDIA "BATAR" DENGAN PENDEKATAN RME BERORIENTASI PADA KEMAMPUAN PEMAHAMAN MATEMATIS MATERI BANGUN RUANG SISI DATAR - Detta Ramadhania Putrie; Syita Fatih ‘Adna; Fadhilah Rahmawati (Jurnal Lebesgue : Jurnal Ilmiah Pendidikan Matematika, Matematika dan Statistika, 2023)
This study aims to determine the validity, practicality, and effectiveness of developing BATAR learning media with the RME approach to help improve mathematical understanding skills. This study uses the ADDIE development model. The subjects of this study were students in grades 8F and 8E at Junior High School 2 Magelang. The results showed that BATAR learning media were in the very valid category with a proportion of 95% of the validity of the material and 87.27% of the validity of the media, the media were in the very practical category with a proportion of 91.27%. Then, the media fulfills the effective aspect with an N-Gain value of 0.71. This can be interpreted that the development of BATAR learning media with the RME approach is stated to be valid, practical and effective